2013
DOI: 10.2147/ijn.s38992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titanium nanoparticles on adhesion, migration, proliferation, and differentiation of mesenchymal stem cells

Abstract: Background:The purpose of this study was to investigate the influences of nanoscale wear particles derived from titanium/titanium alloy-based implants on integration of bone. Here we report the potential impact of titanium oxide (TiO 2 ) nanoparticles on adhesion, migration, proliferation, and differentiation of mesenchymal stem cells (MSC) from the cellular level to the molecular level in the Wistar rat. Methods: A series of TiO 2 nanoparticles (14 nm, 108 nm, and 196 nm) were synthesized and characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Cai et al reported that OBs take up TiO 2 NPs mainly via clathrin-mediated and caveolae-mediated pathways. 82 In addition, as recently described, TiO 2 anatase NPs form bio-complexes with proteins and ions from cell culture medium, which act as a kind of “Trojan-horse” internalization by primary human osteoblasts. 83 Nano-TiO 2 particles (4 and 40 nm) disrupt the cytoskeletal networks and impair migration in Saos-2 cells.…”
Section: Metal Npsmentioning
confidence: 88%
See 1 more Smart Citation
“…Cai et al reported that OBs take up TiO 2 NPs mainly via clathrin-mediated and caveolae-mediated pathways. 82 In addition, as recently described, TiO 2 anatase NPs form bio-complexes with proteins and ions from cell culture medium, which act as a kind of “Trojan-horse” internalization by primary human osteoblasts. 83 Nano-TiO 2 particles (4 and 40 nm) disrupt the cytoskeletal networks and impair migration in Saos-2 cells.…”
Section: Metal Npsmentioning
confidence: 88%
“…Also, osteogenic differentiation was suppressed, characterized by less osteocalcin (OCN) and osteopontin (OPN) expression, weaker ALP activity, and mineralization ability. 82 Interestingly, bigger (196 nm) NPs demonstrated stronger adverse effects than smaller (14 nm and 108 nm) ones, possibly due to higher accumulation of bigger NPs within MSCs. Similarly, Hackenberg et al also reported a significant reduction in migration of TiO 2 NP-treated human MSCs after 3 weeks without affecting their multi-differentiation capacity.…”
Section: Metal Npsmentioning
confidence: 96%
“…10a). The alkaline phosphatase activity, which determines an early mineralization-related protein marker for osteogenesis of osteoblasts, was also increased in the mesenchymal stem cells treated with TiO 2 nanoparticles (14 nm in diameter) after 2 weeks compared to those treated with bigger nanoparticles (108 and 196 nm in diameter) [208]. Biomolecule-TiO 2 nanohybrids can be an advantage due to improving antibacterial and -inflammatory features and biocompatibility without increasing the content of TiO 2 in vital organs.…”
Section: Tissue Regeneration and Chronic Wound Healingmentioning
confidence: 90%
“…The activation of fibroblasts and overproduction of the basic substance were also observed at the reticular layer of these rats (group 1). Severe abnormalities (i.e., damaged epithelium and [208] with permission from the Dove Press Ltd. b The wound-healing process (I) macroscopically analyzed over the course of 19 days, (II) the representative wounds through the healing process for each group, and (III) the optical images of the healed skin from group 1 (A and B), group 2 (C and D), group 3 (E and F), and group 4 (G and H). Numbers indicate tissue structural elements: 1-epidermis; 2-sweat glands; 3scar; 4-derma; 5-hypodermis; 6-hair follicles; 7-sebaceous glands; 8-de-epithelialized scar tissue; 9-scar vessels; 10-inflammatory infiltration in the scar.…”
Section: Tissue Regeneration and Chronic Wound Healingmentioning
confidence: 99%
“…17 After a 14 or 21 day incubation, alizarin red S staining was used to assess calcium deposition by hBMSCs on the bottom of the wells. The deposited calcium was quantified by the spectrophotometry method documented by Cai et al 18 , and the Ca 2þ concentration was determined by comparison with Alizarin Red S standards. Alizarin Red S binds approximately 2 mol of Ca 2þ /mol of dye.…”
Section: Cell Mineralizationmentioning
confidence: 99%